Soft Skills and Hard Skills Needed In Industry 4.0 For Electrical Engineering Students - Sukardi Sukardi; Nizwardi Jalinus; Syaiful Islami; Rizki Hadian Sakti; Husnuzhan Husnuzhan; Anggi Agni Zaus; Mahesi Agni Zaus (Yayasan Riset dan Pengembangan Intelektual (YRPI), 2023)
This paper investigates industry perceptions regarding the relevance of the courses in the curriculum provided by universities and whether they are in accordance with the demands that exist in the industrial world. This research uses a descriptive survey method. The sample taken from electrical engineering alumni who worked in industry was 242 people. This research uses a stratified random sampling technique. The instrument used is a 4-point scale. The assessment was rated Strongly Agree, Agree, Disagree, and Strongly Disagree with weights of 4, 3, 2, and 1, respectively. Three vocational education experts validated the instrument. Reliability was performed with Aiken-V. The questionnaire contains 34 questions. Research data was analysed by percentage, mean, and standard deviation. The findings show that the soft skills and hard skills achieved in each course in the curriculum are arranged in accordance with industry needs. Soft skills and hard skills in the curriculum can be provided to students so that they can look for related jobs.